2012
DOI: 10.1136/emermed-2012-201852
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance demand: random events or predicable patterns?

Abstract: Temporal patterns are present in ambulance demand and importantly these populations are distinct from those found in hospital datasets suggesting that variation in ambulance demand should not be inferred from hospital data alone. Case types seem to have similar temporal patterns across jurisdictions; thus, research where demand is broken down into case types would be generalisable to many ambulance services. This type of research can lead to improvements in ambulance service deliverables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Time of day patterns show a typical bimodal distribution with peaks in the morning and evening and less activity at night [23, 24], which was also present in our data and did not vary by the size of a municipality or year. A higher demand on Fridays [25] and weekends has been found by other authors, especially for alcohol-related and trauma cases [24]. We also observed a slightly higher proportion of emergencies on weekends.…”
Section: Discussionsupporting
confidence: 73%
“…Time of day patterns show a typical bimodal distribution with peaks in the morning and evening and less activity at night [23, 24], which was also present in our data and did not vary by the size of a municipality or year. A higher demand on Fridays [25] and weekends has been found by other authors, especially for alcohol-related and trauma cases [24]. We also observed a slightly higher proportion of emergencies on weekends.…”
Section: Discussionsupporting
confidence: 73%
“…1 The most common methods were either using a telephone triagederived dispatch determinant (most commonly the Medical Priority Dispatch System (MPDS)) [2][3][4][5] or 'a system devised by the authors'. [6][7][8][9][10][11] Categorisation using MPDS occurs at the point-of-call receipt, before ambulance arrival.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of hourly weather measurements were not available. While a broad concordance between temporal events (time of day and weekend/weekday) and transports has been observed across multiple regions (14), the generaliz-ability of weather findings to different geographic regions cannot be fully established. Additionally, the findings from this study may not be easily extrapolated to extreme weather events, such as severe blizzards, as these occurred infrequently during the studied time period.…”
Section: Limitationsmentioning
confidence: 99%
“…Such data would be of value in resource optimization for EMS agencies, where having sufficient staffing and resources is paramount. Previous investigations have identified that day of the week, time of day, and location are associated with utilization of emergency services (14). Additional information on factors impacting EMS demand could inform EMS administrators in ways to better optimize staffing levels to meet the peaks and troughs of EMS demand (15).…”
Section: Introductionmentioning
confidence: 99%